2016
DOI: 10.14742/ajet.1873
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how students perceive the role of ideas for their knowledge work in a knowledge-building environment

Abstract: This study explored how students viewed the role of ideas for knowledge work and how such view was related to their inquiry activities. Data mainly came from students' online interaction logs, group discussion and inquiry, and a survey concerning the role of ideas for knowledge work. The findings suggest that knowledge building was conducive to developing among students a more informed view of ideas that sees ideas as improvable, real-world objects for collaborative and creative knowledge work, rather than mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
(44 reference statements)
0
2
0
1
Order By: Relevance
“…They found that students’ level of participation can be increased with the increase of note creation. Previous studies, such as Lin et al (2017) and Hong and Chiu (2016), found that quantity of ideas, in terms of workability and relevance, is effective in enhancing students’ online collaborative and inquiry performance during the knowledge-building process. Based on these, the quantity of participation and interaction within the online collaborative learning environment can be promoted by increasing the quantity of note-taking, reading and revision.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…They found that students’ level of participation can be increased with the increase of note creation. Previous studies, such as Lin et al (2017) and Hong and Chiu (2016), found that quantity of ideas, in terms of workability and relevance, is effective in enhancing students’ online collaborative and inquiry performance during the knowledge-building process. Based on these, the quantity of participation and interaction within the online collaborative learning environment can be promoted by increasing the quantity of note-taking, reading and revision.…”
Section: Resultsmentioning
confidence: 95%
“…This led us to assume that providing a good structure of learning contents may increase online collaborative dialogue and interaction among students. Furthermore, Lin et al (2017) and Hong and Chiu (2016) have investigated how students’ collaboration toward establishing innovative ideas can promote their perception of ideas quality during the knowledge-building process. They found that an increase in the quality of ideas (in terms of the workability and relevance of ideas) will help in improving the quality of interaction and participation and will create the atmosphere for students to deepen their knowledge about the topic under discussion.…”
Section: Resultsmentioning
confidence: 99%
“…Examina los atributos estructurales específicos de las relaciones que se establecen (Wasserman & Faust, 2013b) y, por lo tanto, se utiliza para identificar a los individuos centrales, prominentes o prestigiosos, dentro de la red (Bihani & Paepcke, 2018;Carceller et al, 2015;Jo et al, 2017;Oh et al, 2018). Estos atributos estructurales reflejan, además, aspectos de la cohesión grupal (Hong & Chiu, 2016;Javadi et al, 2019;Jo et al, 2017;Joksimović et al, 2019;Oh et al, 2018;Sun, Lin, Wu, Zhou, & Luo, 2018) y de la cantidad y calidad de las interacciones sociales dentro de un contexto de red determinado (Chung & Paredes, 2015;Sun et al, 2018).…”
Section: Análisis De Redes Socialesunclassified